2017
DOI: 10.21474/ijar01/3546
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Content and Evaluation of Antioxidant Activity of Anacycluspyrethrum(l.) Lag. From Timahdite a Moroccan Middle Atlas Region.

Abstract: As part of valorisation of medicinal and aromatic plants from Timahdite, a region located in Moroccan Middle Atlas, we focused our study on an endemic species which belongstoAsteraceae family: Anacyclus pyrethrum L. This species, widely used by local people in traditional pharmacopeia, was chosen to conduct phytochemical studies and to assess the antioxidant activity of its roots, leaves and flowers extracts. Thus, the plant was harvested in May 2014. The selected organs (roots, leaves and flowers) of Anacyclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
4
6
0
Order By: Relevance
“…depressus (Ball) Maire. These findings were consistent with the results reported by Cherrat et al [ 49 ], which showed that extracts from genera Anacyclus contained polyphenol and flavonoid contents. The results of polyphenol and flavonoid contents found in the present study were lower than those reported by Sujith et al and Daoudi et al [ 15 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…depressus (Ball) Maire. These findings were consistent with the results reported by Cherrat et al [ 49 ], which showed that extracts from genera Anacyclus contained polyphenol and flavonoid contents. The results of polyphenol and flavonoid contents found in the present study were lower than those reported by Sujith et al and Daoudi et al [ 15 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…The Rm sample had the highest total antioxidant activity with a content of 708.74 ± 11.63 mg AAE/g, while the Cf sample had the lowest activity value (160.33 ± 10.23 AAE/g). These findings were in accordance with those reported in a work by Cherrat et al investigating chemical content in the genera Anacyclus [49].…”
Section: Antioxidant Activitysupporting
confidence: 94%
See 1 more Smart Citation
“…The phytochemical examination of the leaves, flowers, roots and flower heads revealed the presence of alkaloids, reducing the compounds and catechins tannins. In addition, this species contains other chemicals such as gallic tannins, sterols, triterpenes, mucilage, coumarins, geese and holocides [ 27 , 32 ] as well as trace minerals such as Fe, Zn, Cr, Cu, Cd, Pb, and Ni [ 33 ]. The highest content of flavonoids and polyphenols is observed in the flowers compared to the leaves and roots.…”
Section: Phytochemistry Of Anacyclus Pyrethrummentioning
confidence: 99%
“…[14][15] Social isolation leads to a reduced seizure threshold in control animals [16][17] and produces a very severe phenotype in rodents with chronic epilepsy. 18 Because stressful situations-which may explain a more severe phenotype [19][20] -are associated consistently with oxidative stress [21][22] and inflammation, [23][24] and because extracts of A. pyrethrum have established antiinflammatory 25 and antioxidant properties, [25][26] we also tested whether the efficacy of the plant extracts was similar in experimental epilepsy in socially isolated rats with or without positive handling strategy. Since it is not practical to perform video-electroencephalography (EEG) recordings of individual rodents living in a colony, we used positive handling as an approximation of social contact.…”
Section: Introductionmentioning
confidence: 99%